Challenges of a New Zealand information communication technology company in the call center business. - Chua, Bee Luan. (2008)
Analysis of New Zealand’s competitive environment in the call center business using Porter’s (1980) Five Forces. Identification of the critical success factors and challenges of this industry through qualitative studies, literature reviews and interviews.